2005
DOI: 10.1093/tropej/fmi036
|View full text |Cite
|
Sign up to set email alerts
|

Bronchiectasis: the Consequence of Late Diagnosis in Chronic Respiratory Symptoms

Abstract: Bronchiectasis is still common among some developing countries like Turkey. The aim of this study was to document the number of children with non-cystic fibrosis (CF) bronchiectasis, to evaluate the risk factors and to emphasize early diagnosis and treatment. All children, except those diagnosed with CF, with bronchiectasis established by chest radiogram, bronchography and/or computed tomography or biopsy material, were retrospectively reviewed. They were tested for serum total eosinophil count, nasal smear, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0
8

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 13 publications
3
39
0
8
Order By: Relevance
“…Zaid et al 19 reported rate of BE secondary to aspiration as 22% and Li et al 20 as 18%. In the studies from our country, Karadağ et al 16 reported the rate as 3.6% and Doğru et al 18 as 3.4% but Karakoç et al 17 reported no case of BE secondary to aspiration. In our previous study our rate was higher 5 .…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Zaid et al 19 reported rate of BE secondary to aspiration as 22% and Li et al 20 as 18%. In the studies from our country, Karadağ et al 16 reported the rate as 3.6% and Doğru et al 18 as 3.4% but Karakoç et al 17 reported no case of BE secondary to aspiration. In our previous study our rate was higher 5 .…”
Section: Discussionmentioning
confidence: 81%
“…The BE rate secondary to asthma was reported as 31.8% by Gillard et al 22 , as 18.2% by Karakoçet et al 17 , as 11.8% by Doğru et al 18 , and as 4.5% by Karadağ et al 16 in their cases. What may be the reason for the decrease of asthma rates in the present study?…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Karakoc et al found bronchiectasis affecting the left lower lobe in 30.4%, and multilobar involvement in 56.5% (Karakoc et al, 2001). Dogru et al found the most common lobe affected by bronchiectasis was the left-lower lobe in the 204 children they evaluated (Dogru et al, 2005). Isolated upper lobe bronchiectasis generally relates to prior tuberculosis, bronchopulmonary aspergillosis, or bronchial obstruction.…”
Section: Pathophysiologymentioning
confidence: 99%